PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA ASN DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING PADA DINAS KOPERASI PERINDUSTRIAN DAN PERDAGANGAN KABUPATEN SITUBONDO - Martina, Sri; Karnadi, Karnadi; Pramesthi, Riska Ayu (Fakultas Ekonomi dan Bisnis, 2022)
The purpose of this study was to analyze the effect of the variable Influence of Leadership Style and Work Environment on ASN Performance With Schagai Work Motivation Intervening Variable at the Cooperative, Industry and Trade Office of Situbondo Regency by using the Structural Equation Model Partial Least Square 3.0 (PLS). The result of the influence hypothesis test using the Smart PLS 3.0 application. Leadership style has a significant positive effect on work motivation, (H1 is accepted), Work environment has a significant positive effect on work motivation (H2 is accepted), Leadership style has a significant positive effect on ASN performance (H3 accepted), Work environment has a significant positive effect on ASN performance (H4 accepted), Work motivation has a positive significant effect on ASN performance, (H5 is accepted), Leadership style has a positif but not significant effect on ASN performance through work motivation (H6 is rejected), and the work environmnet has a positive but not significant effect on the performance of ASN through work motivation (H7 rejected).